Enhancement of Nonspecific Immune Response and Growth Performance of Litopenaeus vannamei by Oral Administration of Nucleotides (PENINGKATAN RESPONS IMUN NONSPESIFIK DAN PERFORMA PERTUMBUHAN LITOPENAEUS VANNAMEI MELALUI PEMBERIAN NUKLEOTIDA SECARA ORAL) - Manoppo, Henky; ., Sukenda (Jurnal Veteriner; Vol 14 No 4 (2013), 2013)
This research evaluated the nonspecific immune responseand growth of Litopenaeus vannamei fednucleotide diet.  In Laboratory, juveniles were reared in two groups of glass aquaria, each with threereplications.  Shrimps in group one were fed nucleotide diet and in group two were fedpellet four consecutiveweeks. Total Haemocyte Count and Phenoleoxydase activity were evaluated at the end of feeding whilegrowth was measured at two weeks interval. At the end of feeding, shrimps were intramuscularlyinjectedwith Vibrio harveyi  0.1x106 cfu.shrimp-1.  In tambak, juveniles were raised in two groups of net cages(hapa), each with three replications. One group was fed nucleotide diet while the other wasfed pellet forfour weeks. Total Haemocyte Count of shrimp fed nucleotide diet significantly increased up to 87% higherthan shrimps fed pellet.  Phenoleoxydase activity of shrimp fed nucleotides diet also increased isignificantlyas compared to shrimp fed pellet (p=0.02). Higher resistance and growth were observed in shrimp fednucleotide diet. In tambak, weight gain of shrimp fed nucleotide was 35.75% greater than shrimp fedpellet. Survival rate (83.24%) was higher than shrimp fed pellet (81.71%).  As conclusion, oral administrationof nucleotide at 400 mg.kg-1 diet could enhancethe nonspecific immune response, resistance, and growth ofL. vannamei.
Keywords: Litopenaeus vannamei, nucleotides, total haemocyte count, phenoloxidase activity, resistance